1998
DOI: 10.1002/(sici)1097-0274(199802)33:2<123::aid-ajim4>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Methods for investigating age differences in the effects of prolonged exposures

Abstract: People experience physiological changes with age which may lead to changes in sensitivity to many kinds of exposure. In situations of prolonged, low level exposure, differences in the effects of exposures received at different ages may be difficult to evaluate, since study members receive low level exposures over a range of ages. Such investigations require examination of the effects of different age‐patterns of exposure. Three approaches to investigating age‐related variability in the effects of prolonged exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…This is a significant step forward in assessing the potential human toxicity of a class of chemicals known to be reproductive and developmental toxicants in rodents. Improved methods for analysis of exposure, especially of age and time effects, are likely to impact the characterization of occupational exposure in these studies (Richardson and Wing 1998). Current research approaches usually consider the action of single, unique toxicants on outcomes of interest, creating yet another challenge to drafting a reproductive hazards agenda.…”
Section: Estimating Occupational Exposurementioning
confidence: 99%
“…This is a significant step forward in assessing the potential human toxicity of a class of chemicals known to be reproductive and developmental toxicants in rodents. Improved methods for analysis of exposure, especially of age and time effects, are likely to impact the characterization of occupational exposure in these studies (Richardson and Wing 1998). Current research approaches usually consider the action of single, unique toxicants on outcomes of interest, creating yet another challenge to drafting a reproductive hazards agenda.…”
Section: Estimating Occupational Exposurementioning
confidence: 99%
“…An exception to the low overall mortality rates among ORNL workers as compared to the general population, however, is the observed excess mortality due to leukemia and illdefined causes (7,8 (8). Subsequent analyses of that subcohort reported that associations between radiation dose and cancer mortality were primarily due to radiation doses accrued at older ages (10,11,24).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analyses of radiation-mortality associations were conducted using the Poisson regression method (16,11 After evaluation of the data, we determined that a single term could be used to adjust for age at risk centered at 52.5 years in a log-log relationship for cancer causes of death and in a log-linear relationship for noncancer causes (22). This is similar to previous analyses of mortality of workers at the ORNL and has been demonstrated to be an efficient method for adjusting for age at risk (23,24 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a significant step forward in assessing the potential human toxicity of a class of chemicals known to be reproductive and developmental toxicants in rodents. Improved methods for analysis of exposure, especially of age and time effects, are likely to impact the characterization of occupational exposure in these studies (Richardson and Wing 1998).…”
Section: Identifying Hazardsmentioning
confidence: 99%